RobTech - Task 1.3 - Survey in Architectural Design and Construction - José Pedro Sousa (2014)
This report is part of the research project "Robotic Technologies for a Non-Standard Design and Construction in Architecture", supported by the FCT - Fundação para a Ciência e a Tecnologia. In the scope of the introductory activities of the project (T1.1, T.1.2 and T1.3), the present task surveys architectural projects showing pertinent issues regarding material, formal (geometry) or construction. These projects has the potential to inspire interesting challenges to be tackled by means of robotic fabrication technologies.